CO-RELATION OF TOXOPLASMA GONDII INFECTION AND COUSIN MARRIAGES - Lodhi, M. Saqib; Khan, M. Aslam; Ahmed, Manzoor (Journal of Ayub Medical College Abbottabad, 1995)
ABSTRACT Sera from 735 women of child-bearing age (15-45) years) were tested for the presence of IgG antibodies to Toxoplasma gondii by Enzyme-Linked Immunosorbent Assay (ELISA) technique. Along with other information's, the respondents were also asked about the relationship of their parents to each other before marriage. 263 (35.78%) women were seropositive for Toxoplasma antibodies. Seropositivity was much higher (48.63%) in the group whose parents were first cousins and the rate declined progressively in second cousins (41.46%) distant blood relations (26.82%), same caste (26.63%) and different caste (23.73%). This difference is statistically highly significant (P<0.005). The reason for high prevalence of Toxoplasma gondii infection among women whose parents arc first cousins is not clear. Further study in this regard is suggested.